MULHERES ENTRE - VISTAS: UM CONVERSARE INTERGERACIONAL - Maria Alice Nunes Costa; Naiara Coelho; Monique Rodrigues Lopes; Maria Alzira de Oliveira Noli (TRF2, 2018)
This article aims to analyze feminism, from the life history of four women born in three different decades (1930, 1960 and 1990); and with different perceptions about what it is to be a woman and feminism. These women interviewed are the authors of this article. We start from the methodology of structured interview and the history of life as a source of rescue and record of the memory of the experiences of these women. In this sense, this article may collaborate in intergenerational interlocution and in comparative analyzes of different generational positions. We will be focused on personal accounts and perceptions about feminism; male hegemonic power; and about being, living and feeling like a woman in a sexist world. This inter-view will allow the sharing of the cultural narratives of these women and their points of view. Finding a common denominator about feminism among the three different generations in this article will be the challenge of our analysis through the intersection and triangulation of the dialogues constructed organically between them.